Overcoming the drug resistance barrier: progress in fosfomycin combination therapy against multidrug-resistant pathogens - Wu, Yan; Li, Jimin; Qiao, Fengling; Guo, Jinlin; Zhang, Lin; Jia, Xu (Frontiers in Microbiology, 2025)
In the intensifying global crisis of antimicrobial resistance (AMR), the “old” antibiotic fosfomycin has regained prominence because of its unique mechanism of action and potent activity against numerous multidrug-resistant (MDR) pathogens. However, its clinical application is hampered by the rapid emergence of resistance during monotherapy. Rational combination therapy represents a strategic necessity to preserve and enhance the efficacy of fosfomycin. This review systematically analyzes the antibacterial and molecular mechanisms of resistance to fosfomycin, with a focus on the growing threat posed by plasmid-mediated resistance genes. The preclinical and clinical evidence of key combination regimens (including β-lactams, aminoglycosides, fluoroquinolones, polymyxins, and daptomycin) has been comprehensively evaluated, with detailed discussions of the mechanistic foundations for the observed synergistic effects. Although in vitro and animal models show substantial promise, we critically examine the translational gap between positive preclinical results and clinical realities, discussing major barriers to clinical advancement. Finally, we outline a prospective research agenda, encompassing pharmacokinetic/pharmacodynamic (PK/PD)-guided precision dosing, exploring non-antibiotic adjuvants, and developing more predictive preclinical models to unlock the full potential of fosfomycin-based combinations against MDR infections.